Diagnostic utility of flow cytometric immunophenotyping in cerebrospinal fluid specimen. (28th October 2021) - Naiyer, N; Lin, H
Abstract: Introduction/Objective: Flow cytometric immunophenotyping (FCI) of cerebrospinal fluids (CSF) has increasingly been used for diagnosing and monitoring hematologic malignancies. We reviewed CSF specimens sent for flow cytometry evaluation to identify the utility and limitations of FCI. Methods/Case Report: We performed a retrospective review on CSF specimens received from July to October 2020. Samples were sent with requisition for unexplained neurologic signs or symptoms, to determine CNS involvement of neoplasm, or to stage a neoplasm. We reviewed specimen volume and cell count of flow cytometry samples and electronic medical records for possible diagnosis at time of specimen submission, final diagnosis, and concurrent cytology diagnosis. Results (if a Case Study enter NA): A total of 104 CSF samples from 59 patients were processed by the Flow Cytometry Laboratory during the review period. Of the 104 samples, 66% were from patients with a prior history of a hematologic malignancy, of which 20% had abnormal findings by FCI and cytomorphology. FCI was noncontributory for the cases in which patient did not have a previously diagnosed hematologic malignancy and underwent lumbar puncture for neurological abnormalities (n = 34). Concurrent cytology results were available in all but one case. Atypical or reactive findings by cytomorphology were seen in 21 cases (20%), for which flow cytometry studies showed no diagnostic immunophenotype in 12 cases. Abnormal FCI results occurred in 5 cases with history of hematologic malignancies, while concurrent cytomorphologic reports were negative. Conclusion: Our findings suggest that CSF flow cytometry has low utility for screening patients with undifferentiated neurologic symptoms or without a prior hematologic malignancy history. Use as a screening tool for cases without clinical suspicion of hematolymphoid neoplasm is debatable. Flow cytometric and cytomorphologic analysis should be performed concurrently. While flow cytometric analysis in CSF may have higher sensitivity in hematologic malignancies, cytomorphology appears more favorable in identifying atypia or reactive conditions.